Postnatal Developmental Expression Profile Classifies the Indusium Griseum as a Distinct Subfield of the Hippocampal Formation - Sanders, Marie; Petrasch-Parwez, Elisabeth; Habbes, Hans-Werner; Düring, Monika v.; Förster, Eckart (Frontiers in Cell and Developmental Biology, 2021)
The indusium griseum (IG) is a cortical structure overlying the corpus callosum along its anterior-posterior extent. It has been classified either as a vestige of the hippocampus or as an extension of the dentate gyrus via the fasciola cinerea, but its attribution to a specific hippocampal subregion is still under debate. To specify the identity of IG neurons more precisely, we investigated the spatiotemporal expression of Calbindin, Secretagogin, Necab2, PCP4 and Prox1 in the postnatal mouse IG, fasciola cinerea and hippocampus. We identified the calcium binding protein Necab2 as a first reliable marker for the IG and fasciola cinerea throughout postnatal development into adulthood. In contrast, Calbindin, Secretagogin and PCP4 were expressed each with a different individual time course during maturation, and at no time point, IG or fasciola cinerea principal neurons expressed Prox1, a transcription factor known to define dentate granule cell fate. Concordantly, in a transgenic mouse line expressing the fluorescent protein eGFP in dentate granule cells, neurons of IG and fasciola cinerea were eGFP-negative. Our findings preclude that IG neurons represent dentate granule cells, as earlier hypothesized, and strongly support the view that the IG is an own hippocampal subfield composed of a distinct neuronal population.